Towards a face recognition system : face detection, face registration, and head pose estimation - Ying, Ying (2014)
Generally, solutions of face recognition system involve a series of computer vision topics with configurations and connections according to various requirements and emphases. In this dissertation, towards a face recognition system with no cooperation of human beings, face detection, face registration, and head pose estimation are fully and in-depth investigated, especially in the direction of being implemented as practical applications. It is with the aim to free these applications from the flaws in terms of accuracy, robustness, and efficiency that novel algorithms are proposed.